Avaliação do desempenho zootécnico e técnicas de cultivo do Laetacara dorsigera em cativeiro - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
The work was divided into two distinct chapters. In the first chapter, the stocking density was tested on the growth of the Laetacara dorsigera, for which two experiments were carried out The two experiments were conducted in a completely randomized design, with three treatments and four replicates, each lasting 45 days. The first was conducted at densities of 0.25, 0.50 and 0.75 fish L-1 and the second with the best density found in the first experiment, plus densities of 0.30 and 0.40 fish L-1. The following zootechnical parameters were measured: survival rate, average total lengths and average initial and final weights, as well as relative growth rates, specific growth rates and weight gain. There was a significant difference in the first experiment for final length (at densities of 0.25 and 0.50 fish L-1, respectively), TCR% and TCE weight% (0.25 fish L-1) and survival (0.50 fish L-1); in the second experiment there was no significant difference for the densities tested. The aim of the second chapter was to evaluate the use of agro-industrial waste on the productive performance of Laetacara dorsigera. The experimental design was entirely randomized, with 2 treatments consisting of agro-industrial waste (acerola bran and guava bran), with 6 repetitions, lasting 90 days, the same zootechnical parameters were measured and it was found that the averages for relative growth rate, final length (g), specific growth rate, weight gain (g) and final weight gain (g) differed significantly between the treatments, showing not only that the fish were well accepted to include the guava residue, but also that they developed uniformly at the 30% inclusion level.
Keywords: Peixes - Criação; Aquicultura; CIENCIAS AGRARIAS; Aquarismo; Amazônia; Resíduo; Nutrição; piscicultura ornamental